Project-based learning in vocational schools: A meta-analysis study - Nuryani Dwi Astuti; Yuli Prihatni; Ari Setiawan; Heri Retnawati; Risky Setiawan; Dita Surwanti; Joko Supriyanto (Research and Social Study Institute, 2026)
Project-Based Learning (PBL) have shown significant results in increasing students’ mathematical skill. In a meta-analysis involving 17 studies, the results show that PBL significantly increases the students’ mathematical skills. The results of the fixed and random effects analysis show that the overall coefficient model and the residual heterogeneity are significant. The coefficient estimation for the intercept within the model is 71.872, which shows that when all independent variables are worth to zero, the dependent variable is worth estimated to 71.872. A very small p-value (< 0.001) indicates that the results are statistically very significant. The models have a good fit with the observational data, but it could not explain the variation between studies. There is a high level of heterogeneity among studies and there is not any indication of publication bias in the analysis. Thus, the results show that PBL basically can increase the students’ mathematical skills. However, it is necessary to consider other factors that can influence the results.